Combating corruption in Malaysia: an analysis of the anti-corruption commission act 2009 with special reference to legal enforcement body / Wan Murshida Wan Hashim and Mazlena Mohamed - Wan Hashim, Wan Murshida; Mohamed, Mazlena (Universiti Teknologi MARA, 2019)
Having a specific enforcement body to tackle corruption constitutes one of the significant initiatives in the effort to fight the matter. As such, a comprehensive and effective law should be enacted for the said matter and any enforcement body established thereunder must be seen capable to fight corruption effectively. In Malaysia, a body governing the matter known as Malaysian Anti-Corruption Commission has been established by virtue of the law passed by the government namely the Malaysian Anti-Corruption Act 2009. Being the main legislation governing corrupt practices in Malaysia, the Act provides amongst others, provisions governing the Commission and other bodies established thereunder. This paper provides a doctrinal analysis of the Malaysian Anti-Corruption Commission Act 2009 with special reference to the provisions governing legal enforcement body so much so that it provides an insight into its efficacy. The findings revealed that there are some loopholes in the laws by which could result in vitiating the efficacy of the legal enforcement body to combat corruption in Malaysia.